Penanganan pembiayaan bermasalah dalam mengelola risiko pembiayaan murabahah di perbankan syariah - Arnanda, Putri Amalia (Maliki Interdisciplinary Journal, 2024)
Risk management is an important aspect in sharia banking operations, especially in the context of murabahah financing. The aim of this research is to find out strategies for reducing risks in murabahah financing and ways to handle financing problems in murabahah financing. The research method uses qualitative methods with literature studies. The sampling method used is purposive non-probability, with 2 types of samples grouped, namely decision and quota samples. The research results show that the right strategy to reduce risk in murabahah financing is to analyze the character, capacity, capital, collateral and conditions of prospective customers. Handling problematic financing in murabahah financing can be done through intensifying collections, giving warnings, revitalization processes, and resolving collateral. Thus, risk management plays an important role in maintaining the health and sustainability of sharia banking operations.